Penerapan Media Visual Untuk Meningkatkan Hasil Belajar Tematik Tema Keselamatan Di Rumah dan Di Perjalanan Siswa Kelas II SDN 19 Mataram Tahun Ajaran 2022/2023 - Rosidah Rosidah; Muhammad Tahir; Irma Suyatna Rizki (Journal of Science Instruction and Technology, 2023)
This classroom action research was motivated by the low results of thematic learning for theme 8 "Safety at Home and Travel" in class II at SDN 19 Mataram in 2022/2023. The lack of use of media in learning activities, monotonous learning methods, and the teacher's tendency to dominate which can be seen in teacher interactions with students are one of the factors for low student learning outcomes. This research aims to improve thematic learning outcomes for theme 8 through the use of visual media in learning activities. This type of research is Class Action Research (PTK) which is carried out in two cycles and through four stages in a recyclable manner, namely class action planning, implementation of class action learning, observation/observation, and reflection. The research subjects were 2nd grade students at SDN 19 Mataram with a total of 12 students. Data collection methods use questionnaires, documentation and tests. Data collection techniques in this research used observation and test techniques. Meanwhile, the data analysis technique uses descriptive qualitative and quantitative. The results of the research analysis concluded that between cycle I and cycle II there were significant differences and there was an increase in cycle II. In cycle I, the average score obtained by students was 64.4 with a completeness presentation of 58.3%, while in cycle II the average score obtained was 80.8 with a completeness presentation of 83.3% (cycle II). Teacher activity increased during two cycles, namely from the good category to the very good category. Student activity increased during two cycles, namely from the less active category in cycle I and to the active category in cycle II. Based on these results, it can be concluded that the use of visual media can improve the thematic learning outcomes of 8 class 2 students at SDN 19 Mataram for the 2022/2023 academic year.